CONSISTENCY BETWEEN THE PRINCIPAL'S SUPERVISION AND INSTITUTIONAL GOALS - Prasetyo, Purcahyono Hari; Rohmad, Rohmad (STKIP PGRI Situbondo, 2024)
This research aims to determine whether there is consistency between the supervision of school principals and educational objectives at the Nusawungu State Vocational High School, Cilacap district. This research uses a qualitative phenomenological method with the subjects and data sources involved, namely the school principal, deputy principals, vocational heads and teachers. From the research results, it was found that teaching supervision carried out by school principals, deputy principals and vocational heads was carried out in three stages, namely (1) planning by making a supervision schedule, each supervisor and teacher who would be supervised knew the schedule, (2) implementation, at this stage each supervisor supervises several teachers, (3) evaluation, at this stage each supervisor and teacher has obtained supervision notes as evaluation material. Based on the research results, it is known that there is consistency between the principal's supervision and the institution's objectives at the Nusawungu State Vocational High School, Cilacap district.